Fintech peer-to-peer lending mobile application development - Oon, Wei Kin (2022)

(untitled)
This project is a mobile application about peer-to-peer lending as final year project in UTAR for academic purpose. The project will provide students with knowledge and experience in developing mobile applications and designing user interfaces and databases. Mobile application is becoming increasingly common because of its portability and mobility to access everywhere and at any time. This is one of the main reasons that I decide to develop a peer-to-peer lending mobile application. The peer-to-peer loan applications offer both the borrower and the lender the opportunity to select the loan or investment they wish to opt for. Compared to traditional lending methods, peer-to-peer lending applications make the lending and borrowing process more practical. The purpose of this project is to make loan generation faster and provide low loan interests to users. Under the traditional lending method, borrowers had to come to the bank to request a loan. By using this application, the process of application lying for a loan will become faster and convenient. Borrowers can request a loan on the lending platform without going anywhere, just need to download this application. For investors, they can have a look on every request that posted by borrowers and choose the most suitable one to invest. As a result, lending works has taken great care to make our application process as easy and timely as possible. The methodology use for this project is Prototyping. The prototyping model is a systems development process in which a prototype is produced, tested, and changed as needed until an acceptable output is obtained from which the whole system or product may be developed. This paper presents some of the relevant literature reviews, research analysis, research findings and findings of this study.